An Ontology based Optimized Semantic Web Service Discovery using TensorFlow in Overlay Cell Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Semantic Web Services (SWS) proposes to expand traditional web service technology to integrate ontology and semantics. Services adapt to changes without human intervention. The dissemination of information about traffic services is very important to the average consumer. The current system provides semantic web services for travel information through ontology at the request of travelers. However, the current system has problems with high-level semantic web services using the Palochi algorithm. So it does not provide proper services and reliability is declining. To overcome this error, Word Sense Disambiguation (WSD) suggests that, under certain circumstances, semantic similarity results should be improved by reducing ambiguity. Introduced the Genetic Algorithm (GA) to improve optimally based web services. The focus is on providing road accident information through oncology. It selects close to the right services and provides high quality services in terms of fast response time and high accuracy results.